2023
DOI: 10.1515/opag-2022-0205
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trade potential and factors influencing chili export in Indonesia

Abstract: The aim of this study is to analyze the factors that affect the export of chili in Indonesia, determine the most dominant factor, and also the export potential of chili in the importing country. The analytical methods used are panel data analysis with gravity model and trading potential analysis. The results show that the independent variables that significantly affect Indonesia’s chili exports are Indonesia’s real GDP/capita, the real GDP/capita of the destination country, the rupiah exchange rate against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…This finding is slightly weaker than the fuel price effect on Indonesia's exports. This finding aligns with Thorbecke & Sengonul (2023), who found a significant effect of exchange rate on export and import in Turkey, and Sundari et al (2023), who found IDR exchange rate effect on chili export in Indonesia. In Chile, the exchange rate has also been found to predict the return of oil exports (Pincheira-Brown et al, 2022), while in Indonesia, the depreciation of the IDR exchange rate stimulated export in 2015 (Yusuf & Sumner, 2015).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is slightly weaker than the fuel price effect on Indonesia's exports. This finding aligns with Thorbecke & Sengonul (2023), who found a significant effect of exchange rate on export and import in Turkey, and Sundari et al (2023), who found IDR exchange rate effect on chili export in Indonesia. In Chile, the exchange rate has also been found to predict the return of oil exports (Pincheira-Brown et al, 2022), while in Indonesia, the depreciation of the IDR exchange rate stimulated export in 2015 (Yusuf & Sumner, 2015).…”
Section: Resultssupporting
confidence: 90%
“…A high exchange rate equals high production costs due to imported raw materials and capital goods. This finding aligns with Spahiu & Durguti (2023), who found a damaging impact of high-interest rates on export, as well as Thorbecke & Sengonul (2023) and Sundari et al (2023), who found a significant effect of exchange rate on export. However, despite the negative impact of both variables, Bank Indonesia implemented its supervisory role in the IDR exchange rate well, resulting in Indonesia's growing export post-Covid-19 pandemic and the ongoing Russia-Ukraine war.…”
Section: Resultssupporting
confidence: 88%